Modulation of DNA damage tolerance in Escherichia coli recG and ruv strains by mutations affecting PriB, the ribosome and RNA polymerase - Mahdi, Akeel A.; Briggs, Geoffrey S.; Lloyd, Robert G. (Wiley, 2012)
RecG is a DNA translocase that helps to maintain genomic integrity. Initial studies suggested a role in promoting recombination, a possibility consistent with synergism between recG and ruv null alleles and reinforced when the protein was shown to unwind Holliday junctions. In this article we describe novel suppressors of recG and show that the pathology seen without RecG is suppressed on reducing or eliminating PriB, a component of the PriA system for replisome assembly and replication restart. Suppression is conditional, depending on additional mutations that modify ribosomal subunit S6 or one of three subunits of RNA polymerase. The latter suppress phenotypes associated with deletion of priB, enabling the deletion to suppress recG. They include alleles likely to disrupt interactions with transcription anti-terminator, NusA. Deleting priB has a different effect in ruv strains. It provokes abortive recombination and compromises DNA repair in a manner consistent with PriB being required to limit exposure of recombinogenic ssDNA. This synergism is reduced by the RNA polymerase mutations identified. Taken together, the results reveal that RecG curbs a potentially negative effect of proteins that direct replication fork assembly at sites removed from the normal origin, a facility needed to resolve conflicts between replication and transcription.